Risk Map for Facility Siting of an Ammonia-Urea Complex (Journal of Chemical Engineering, 2017)
In this study safer facility siting of an ammonia-urea complex is demonstrated by risk mapping. This risk map is useful for identifying safer zones within the plant at the design stage as well as before setting temporary shelters, i.e. shelters for contractors and maintenance workers etc. in an existing plant. To prepare the risk map a number of critical process units of an ammonia- urea complex are selected as the sources of toxic release and blast overpressure. Locations of control room and three operators shelters are considered with respect to five critical units. Consequences of toxic release and blast overpressure are modeled for various worst case scenarios developed in the critical units. Both structural damage and human mortality/injury are converted into risk scores. Risk mapping of the battery limit area are done and locations with minimum risk scores within plant area are identified for the probable siting of the control room and operators shelters. The findings are compared with the layout of an existing ammonia-urea complex. It is also shown that a simple risk mapping of the plant area is helpful in avoiding facility siting in high risk zone at the same time finding safer locations for different facilities.Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 56-60